2016
DOI: 10.21566/tarbitderg.281887
|View full text |Cite
|
Sign up to set email alerts
|

Sığır veya Koyun ile Otlatılan Eskişehir Ovası Taban Meralarının Bitki Örtülerinin Karşılaştırılması

Abstract: This research was carried out in Eskişehir Plain in 2014, to compare sub-irrigated rangelands vegetation of Eskişehir Plain which have been grazing by sheep and cattle. Measurements were made according to loop method with 40 transect for each rangeland sites in the period of dominant species flowering. In both rangeland sites, it was estimated that Bermuda grass was dominant, Common rush could be suppressed by sheep grazing and species composition was different at rangeland vegetation depend on grazing animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
3
7
0
1
Order By: Relevance
“…This difference between two studies can be related to the structural difference between the studied rangelands (semi-mountainous and lowland rangelands vs. highland or upland rangelands) and the GAS (goat, sheep and cattle herds vs. sheep and cattle herds) in MSG system. The rangeland condition and canopy data in the present study indicate that the SSG and MSG rangelands were overgrazed, as reported by Koç and İleri (2016). As noted by Animut et al (2005) and in Experiment I, overgrazing suppresses the desirable pasture species, which can allow undesirable species like shrub and weeds to establish while high stocking rates limits forage selectivity and forces the animals to consume all species present.…”
Section: 2 Experiments IIsupporting
confidence: 76%
See 4 more Smart Citations
“…This difference between two studies can be related to the structural difference between the studied rangelands (semi-mountainous and lowland rangelands vs. highland or upland rangelands) and the GAS (goat, sheep and cattle herds vs. sheep and cattle herds) in MSG system. The rangeland condition and canopy data in the present study indicate that the SSG and MSG rangelands were overgrazed, as reported by Koç and İleri (2016). As noted by Animut et al (2005) and in Experiment I, overgrazing suppresses the desirable pasture species, which can allow undesirable species like shrub and weeds to establish while high stocking rates limits forage selectivity and forces the animals to consume all species present.…”
Section: 2 Experiments IIsupporting
confidence: 76%
“…The BC of the SSG and MSG rangelands consisted of a mixture of 54 and 36 plant families, respectively, dominated by Fabaceae, Poaceae, Asteraceae and Rosacea based on the frequencies of families (Table 3). As reported by Koç and İleri (2016), species composition was different at rangeland vegetation depend on the GAS. In the previous studies in Turkey (Yavuz et al, 2012;Çınar et al, 2014;Ünal et al, 2014;Uzun et al, 2015;İspirli et al, 2016;Seydoşoğlu et al, 2018), it has been noted that the abundance of invasive species in the BC of rangelands is high due to both regional conditions and utilization methods (Seydoşoğlu et al, 2018), which is an indicator of overgrazing.…”
Section: 2 Experiments IIsupporting
confidence: 57%
See 3 more Smart Citations